Implementation of Plea Bargaining in the Indonesian Criminal Justice System - Nurana, Desi (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
There is a need for a new system in the Indonesian Criminal Justice System that is thought to make case handling more efficient, specifically by adopting plea bargaining as a problem-solving method for the Indonesian criminal justice system. In this study, the issue formulation is how to implement plea bargaining in the present criminal justice system and the urgency of plea bargaining in the renewal of the Indonesian criminal justice system. The Normative Juridical Research technique was employed to generate this research. Normative Juridical Research is a type of legal research that involves literature study or just secondary information. The regulation on the application of Plea Bargaining in the current criminal justice system is not based on the value of justice, as Article 4 paragraph (2) of Law No. 48 of 2009 concerning Judicial Power mandates that the judicial process must be carried out quickly. At a low cost, but based on the problems that the author described in the previous sub-chapter, the criminal justice process has not been able to reach a simple judicature to this day. The complexity of the criminal justice process in Indonesia now prevents simple, quick, and low-cost judicial implementation from being accomplished in the criminal justice process in Indonesia. In this case, there is a need for a renovation of Indonesia's criminal justice system. This is the legal basis for the urgent need to establish Plea Bargaining in Indonesia.